Sulfur oxidation state and solubility in silicate melts - Boulliung, J; Wood, B (Springer Nature, 2023)
We have determined the solubility of sulfur (S) as sulfide (S2–) for 13 different natural melt compositions at temperatures of 1473–1773 K under controlled conditions of oxygen and sulfur fugacities (fO2 and fS2, respectively). The S and major element contents of the quenched glasses were determined by electron microprobe. The sulfide capacity parameter (CS2–) was used to express S2– solubility as a function of the oxygen and sulfur fugacities according to the equation: log CS2− = log Smelt(wt%) + 0.5 log ( fO2 fS2 ) . Sulfide capacities of silicate melts were found to increase with temperature and the FeO content of the melt. We combined our sulfide data at 1473–1773 K with (O’Neill and Mavrogenes, J Petrol 43:1049– 1087, 2002) results at 1673 K, and obtained by stepwise linear regression the following equation for sulfide capacity log CS2− = 0.225 + (25237XFeO + 5214XCaO + 12705XMnO + 19829XK2O − 1109XSi0.5O − 8879)∕T . XMO is the mole fraction of the oxide of M on a single-oxygen basis, and T is in Kelvin. The sulfide capacity equation was combined with sulfate capacity (CS6+) data for similar compositions and at the same temperatures (Boulliung and Wood, Geochim Cosmochim Acta 336:150–164, 2022), to estimate the S redox state (S6+/S2– ratio) as a function of melt composition, temperature and oxygen fugacity. Results obtained are in good agreement with earlier measurements of S6+/S2– for basaltic and andesitic compositions. We observe a significant increase, however, relative to FMQ of the oxygen fugacity of the S2– to S6+ transition as temperature is lowered from 1773 to 1473 K. We used our results to simulate sulfur-degassing paths for basaltic compositions under various redox conditions (FMQ –2 log fO2 units to FMQ + 2). The calculations indicate that, given an initial concentration of 0.12 wt% S in an ascending melt at 250 MPa, most of the S (> 80%) will be degassed before the magma reaches 100 MPa pressure.